Removal efficiency of calcium hydroxide intracanal medicament with RinsEndo system in comparison with passive ultrasonic irrigation, an in vitro study - Khademi, Abbass Ali (Dent Res J (Isfahan), 2015)
BACKGROUND: Different techniques have been introduced to improve removing the calcium hydroxide intra-canal dressing. The purpose of this study was to compare the efficiency of passive ultrasonic irrigation (PUI) and RinsEndo system in the removal of calcium hydroxide from root canal system. MATERIALS AND METHODS: Access cavities were prepared in 50 single-rooted anterior teeth. Cleaning and shaping were done using the Flexmaster rotary system up to size no. 30, 6%. The canals were filled with injectable calcium hydroxide (calcipex). After 7 days, the calcium hydroxide were retrieved using RinsEndo system in Group 1 (n = 20), with PUI system in Group 2 (n = 20). In positive control group (n = 5), no irrigation was performed. In negative control group (n = 5), root canals were not filled with any medicament. Following the removal of the calcium hydroxide with these two systems, teeth were split buccolingually into two sections and every third of the root canals was evaluated under stereomicroscope (×30) to analyze the residual medicament in each segment. Data were analyzed using the Kruskal-Wallis and Mann-Whitney tests (P < 0.05). RESULTS: There was no significant difference in the removal of calcium hydroxide between RinsEndo and PUI at cervical (P = 0.67), middle (P = 0.51) and apical (P = 0.75) part of the root canals. CONCLUSION: None of the irrigation techniques was able to completely remove calcium hydroxide from the root canal system.